2013
DOI: 10.1007/978-3-642-39112-5_117
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous Examples as Desirable Difficulty

Abstract: Abstract.Erroneous examples, an unusual and challenging form of learning material, are arguably a type of desirable difficulty for students that could lead to deeper learning. In a series of studies we have done over the past three years involving web-based math instruction, the learning benefits of erroneous examples we have observed occured on delayed tests, as occurs in the desirable difficulties literature. This short paper briefly reviews the literature, summarizes our results, and speculates on how an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Some prior work on incorrect worked examples suggests that benefits occur at a delay rather than immediate posttest (Adams et al, 2014; Durkin & Rittle‐Johnson, 2012). These delayed benefits are explained as being a result of desirable difficulties while working with errors invoking deeper processing of material which would not show immediate benefits but rather deeper learning over time (Adams, McLaren, Mayer, Goguadze, & Isotani, 2013). Prior work has demonstrated that altering instruction to make it more challenging during learning leads to long‐term benefits (Bjork & Bjork, 2011; Schmidt & Bjork, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Some prior work on incorrect worked examples suggests that benefits occur at a delay rather than immediate posttest (Adams et al, 2014; Durkin & Rittle‐Johnson, 2012). These delayed benefits are explained as being a result of desirable difficulties while working with errors invoking deeper processing of material which would not show immediate benefits but rather deeper learning over time (Adams, McLaren, Mayer, Goguadze, & Isotani, 2013). Prior work has demonstrated that altering instruction to make it more challenging during learning leads to long‐term benefits (Bjork & Bjork, 2011; Schmidt & Bjork, 1992).…”
Section: Discussionmentioning
confidence: 99%